Facts about Chromium - Linda B. Bobroff (EDIS)
FCS8803, a 2-page fact sheet by Linda B. Bobroff, explains why we need chromium (a mineral) and how much we need, and covers the question of chromium supplementation. Published by the UF Department of Family, Youth and Community Sciences, December 2006.